2020
DOI: 10.1111/1346-8138.15309
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cutaneous adverse events and prognosis in patients with melanoma treated with nivolumab: A single institutional retrospective study

Abstract: Treatment for patients with unresectable melanoma has been dramatically changed by the use of immunocheckpoint inhibitors (ICI). In this study, we reviewed patients with unresectable stage III/IV melanoma, who were treated with nivolumab between and retrospectively recorded cutaneous adverse events (cAE), development of vitiligo, clinical characteristics and clinical responses. We identified 128 patients, 61 (47.7%) of whom showed cAE, including 30 (23.4%) with development or exacerbation of vitiligo. The prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…3), including acral ( n = 2) [42,44], mucosal ( n = 1) [37,42], or uveal ( n = 1) [29]. Three additional studies [31,32,38] did not specify histology but were conducted in Asia, where acral or mucosal melanoma is the dominant subtype.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3), including acral ( n = 2) [42,44], mucosal ( n = 1) [37,42], or uveal ( n = 1) [29]. Three additional studies [31,32,38] did not specify histology but were conducted in Asia, where acral or mucosal melanoma is the dominant subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4a describes resistance by treatment regimen and country/region. In the studies with cohorts in Asia, where patients are predominantly acral and mucosal melanoma [47], the median primary resistance for patients treated with anti-PD-1 monotherapy overall (line of therapy not specified) was 50.78% (35.53-66.67%; n = 4) [31,32,38,44]. In the studies conducted in Europe, one study assessed primary resistance in first-line monotherapy (39.13%) [21]; the median primary resistance for patients treated in second-line was 41.54% (30.0-56.41%; n = 3) [23][24][25]; in the studies that did not specify line of therapy, the median primary resistance was 48.32% (28.57-81.25%; n = 9) [24,26,29,33,36,40,41,43,48].…”
Section: Primary Resistance To Anti-pd1 Monotherapy By Line Of Therap...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a well-documented relationship between checkpoint-inhibitor induced cutaneous toxicity, specifically vitiligo, and improved tumor response. [21][22][23] A retrospective study of 346 patients with melanoma showed that those who developed gastrointestinal immune adverse events had a statistically significant improvement in progression-free and overall survival compared to those who did not. 24 Moreover, the severity of the irAE appeared to correlate with benefit: patients who developed higher-grade diarrhea had a statistically significant improvement in overall survival.…”
Section: Pathophysiology Of the Development Of Iraesmentioning
confidence: 99%